An Improved Equation for Predicting Compressive Stress in Posttensioned Anchorage Zone - Park, Young Ha; Kim, Moon Young; Park, Jong Myen; Jeon, Se Jin (Advances in Civil Engineering, 2020)
Validity of the approximate equation for predicting compressive stress in the posttensioned anchorage zone presented in the AASHTO LRFD Bridge Design Specifications was investigated in this study. Numerical analysis based on the finite element method (FEM) and theoretical analysis showed that the AASHTO formula gives relatively accurate stress values when the effect of duct holes is neglected. However, it was found that the formula can significantly overestimate the stresses in the actual prestressed concrete member with spaces occupied by ducts. Therefore, an improved equation was proposed for the existing AASHTO equation to consider the effect of the duct holes on the stress distribution. This resulted in relatively accurate prediction of the distribution and magnitude of the compressive stresses even with the presence of the duct holes. The proposed equation was also validated by comparing with the stresses measured in the test of a posttensioned full-scale specimen. This study is expected to contribute to the design of the anchorage zone in prestressed concrete structures by suggesting a more reasonable way to assess the appropriateness of anchorage devices.